Growth and Immune Evasion of Lymph Node Metastasis - Jones, Dennis; Pereira, Ethel R.; Padera, Timothy P. (Frontiers in Oncology, 2018)
Cancer patients with lymph node (LN) metastases have a worse prognosis than those without nodal disease. However, why LN metastases correlate with reduced patient survival is poorly understood. Recent findings provide insight into mechanisms underlying tumor growth in LNs. Tumor cells and their secreted molecules engage stromal, myeloid, and lymphoid cells within primary tumors and in the lymphatic system, decreasing anti-tumor immunity and promoting tumor growth. Understanding the mechanisms of cancer survival and growth in LNs is key to designing effective therapy for the eradication of LN metastases. In addition, uncovering the implications of LN metastasis for systemic tumor burden will inform treatment decisions. In this review, we discuss the current knowledge of the seeding, growth, and further dissemination of LN metastases.